2015
DOI: 10.1007/s40368-015-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the location of the mandibular and mental foramen in children with Mongoloid skeletal pattern

Abstract: With advancing age and growth, the position of MF remained constant at the ramus with tendency to move from below to at the level of occlusal plane, while mf moved distally and inferiorly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
3
10
0
5
Order By: Relevance
“…The findings of this study were in accordance with the results of Lim et al' study which found mental foramen position changed during primary dentition and remained mostly stable during the eruption of the primary and mixed dentitions [20]. Our samples were above 18 years of age; therefore, the distance from mental foramen to midline and inferior border of mandible was constant between different ages.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study were in accordance with the results of Lim et al' study which found mental foramen position changed during primary dentition and remained mostly stable during the eruption of the primary and mixed dentitions [20]. Our samples were above 18 years of age; therefore, the distance from mental foramen to midline and inferior border of mandible was constant between different ages.…”
Section: Discussionsupporting
confidence: 91%
“…, which is similar to the study by Rashid et al 201111 , Samanta PP2013 13 andLinganna CS20158 .In our study the mandibular foramen shows a shift with age which is similar to the study byLim MY et al7 . The observation found in our study was a posterior shift because we studied adult population whereas in the study by Lim MY et al 20157 ,the population studied were children. When compared between genders the mean values superoinferiorly were higher in males than females which is similar to the study conducted by Shendakar AT etal, 201014 .…”
supporting
confidence: 92%
“…On average, the mandibular foramen was 3.1 ± 2.6 mm above the occlusal plane, which is consistent with our results. In the same way, in a population of children with Mongoloid skeletal pattern, Lim [18] described a higher percentage of MF located below the OP under 9 years, and above in older children. In line with our results, Paryab [17] confirmed this position of MF 3-4 mm above the mandibular plane in mixed dentition (from Hellman's stages IIA to IVA), whether the patients were retrognathic or not.…”
Section: Discussionmentioning
confidence: 73%
“…and the reference landmarks are sometimes difficult to identify clinically, especially in children [6,[11][12][13][14]. Previous attempts to determine the position of the MF relative to the occlusal plane have mainly been based on dry mandibles [7,15,16] or on 2D radiographs which were deformed (panoramic radiographs [6,[11][12][13][14][17][18][19]) and/or had a high level of anatomical superimposition (lateral cephalometric radiographs [20,21]). Nowadays, the development of 3D computer software combined with computed tomography (CT) allows indisputable data on the mandibular foramen location to be produced [10,[22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%